The moderating role of job satisfaction in the relationship between workplace happiness and corporate belonging consciousness: The example of the 4th Regional Directorate of Nature Conservation and National Parks - Hasan Alkan; Murat Özen; Gökhan Topaloğlu (Turkish Journal of Forestry, 2025)
There are many different factors affecting the success and sustainability of institutions. Effective personnel management and activities that increase the relationship between the personnel and the institution are among them. People being successful in their work not only provides individual satisfaction but also affects institutional success. Indeed, it is expected that the personnel being happy at work, having high job satisfaction and high levels of institutional commitment will contribute positively to institutional development. This research was conducted to determine the moderating role of job satisfaction in the relationship between workplace happiness and institutional sense of belonging among the personnel (145 technical personnel and 182 administrative personnel) working in the 4th Regional Directorate of Nature Conservation and National Parks and affiliated branch directorates. The research universe consists of 327 people and a survey was conducted with 93 participants. The data in the research was collected using the survey technique. SPSS 22 and AMOS statistical package programs were used in the analysis of the data. Factor analysis, correlation analysis, regression analysis and structural equation model, as well as confirmatory factor analysis, path analysis and moderating effect analysis were used in the research. According to the research findings, it was determined that job satisfaction has a moderating effect on the relationship between workplace happiness and corporate sense of belonging.